Distortion-corrected posterior ocular shape in myopic eyes assessed by ultrawide OCT detects deformations associated With vision-threatening changes - Tan, Bingyao; Shah, Janika N.; McNabb, Ryan P.; Jayaraman, Swathi; Wong, Damon; Chua, Jacqueline; Ang, Marcus; Saw, Seang Mei; Jonas, Jost B.; Kuo, Anthony N.; Hoang, Quan V.; Schmetterer, Leopold (Investigative ophthalmology & visual science, 2024)
To develop a quantitative tool for assessing the posterior ocular shape using widefield, volumetric optical coherence tomography (OCT) in eyes with myopia. This observational, cross-sectional study included 178 eyes from 113 participants. Participants underwent a standardized eye examination, including ocular biometry and a custom ultrawide OCT. True ocular shape was reconstructed by tracing the beam propagation from the system to the posterior eye. Gaussian curvature quantified the localized ocular shape, which was further categorized into five distinct categories. An ocular shape irregularity (OSI) was calculated using principal component analysis. Linear regression with breakpoints analyzed the relationship between ocular shape parameters and axial length (AL). Increased curvature mean and variance were associated with more severe myopia (P < 0.001). Curvature categories (convex, normal, concave, and highly concave) differed significantly between the groups (all P < 0.001). Their correlations with AL revealed significant breakpoints between 27.1 and 27.2 mm. OSI, as a single metric for quantifying ocular shape distortion, was associated with more severe myopia (P < 0.001), and its correlation with AL revealed a breakpoint at 27.2 mm with a fourfold increase in slope steepness beyond this pivot. Determination of OSI was highly reproducible and could also be obtained with fewer scans. Eyes exceeding 27.2 mm in length exhibit pronounced shape changes. Our framework can be seamlessly integrated into commercial OCTs for ocular shape deformation detection, which could aid in identifying eyes with pathologic myopia.
Gesehen am 15.05.2025